Assessment of the Quality of Life of Low-Vision Patients in Benin-City, Edo-State - Odjimogho, Stella E.; Chibuzo, Nkem Victor; Odjimogho, Sunny E.; Gabriel, Benjamin Ogunma (Darul Yasin Al Sys, 2025)
This study was aimed at assessing the impact of low vision on the quality of life of low-vision patients and how rehabilitation and low-vision aids helped improve the Quality of life of these patients. The study employed a cross-sectional study design, which involved using a well-structured questionnaire distributed to low-vision patients seen in the University of Benin Optometry clinic and Echos Hospital limited, Benin City. Data was collected to ascertain the level of low vision, and its impact on the quality of life of patients. This was by examining the functional independence of the patients, their psychosocial well-being and outcomes and ability to catty out vision-specific activities to provide a better understanding of how low vision affects the quality of life of low vision patients. The mean score of participants on the general health and general vision subscales were 59.58 ± 19.03 and 54.58 ± 15.83 respectively. Participants’ responses to the level of ocular pain they experienced was 63.33 ± 17.04. The mean score of participants for distance activities was 58.33 ± 15.72 while that for near activities was 59.64 ± 17.08201. Mean scores for social functioning, mental health and dependency were 70.83 ± 18.95, 36.25 ± 23.92 and 37.78 ± 30.54 respectively. The mean scores for color vision and peripheral vision were 97.50 ± 7.63 and 73.33 ± 25.37. Low vision has effects on vision-specific abilities, and general health as well as mental health effects on patients and rehabilitation services should be made available to curtail these effects. This study provided insight into the effect of low vision on the quality of life and the potential benefits and challenges associated with visual rehabilitation initiatives. It will also contribute to valuable information which will improve the support system for low vision in the community.